Graphdiyne as a promising material for detecting amino acids - Chen, Xi; Gao, Pengfei; Guo, Lei; Zhang, Shengli (Scientific reports, 2015)
The adsorption of glycine, glutamic acid, histidine and phenylalanine on single-layer graphdiyne/ graphene is investigated by ab initio calculations. The results show that for each amino acid molecule, the adsorption energy on graphdiyne is larger than the adsorption energy on graphene and dispersion interactions predominate in the adsorption. Molecular dynamics simulations reveal that at room temperature the amino acid molecules keep migrating and rotating on graphdiyne surface and induce fluctuation in graphdiyne bandgap. Additionally, the photon absorption spectra of graphdiyne-amino-acid systems are investigated. We uncover that the presence of amino acid molecules makes the photon absorption peaks of graphdiyne significantly depressed and shifted. Finally, quantum electronic transport properties of graphdiyne-amino-acid systems are compared with the transport properties of pure graphdiyne. We reveal that the amino acid molecules induce distinct changes in the electronic conductivity of graphdiyne. The results in this paper reveal that graphdiyne is a promising two-dimensional material for sensitively detecting amino acids and may potentially be used in biosensors.